Immunotherapeutic implications on targeting the cytokines produced in rhinovirus-induced immunoreactions - Sang, Le; Gong, Xia; Huang, Yunlei; Zhang, Linling; Sun, Jian (Frontiers in Allergy, 2024)
Rhinovirus is a widespread virus associated with several respiratory diseases, especially asthma exacerbation. Currently, there are no accurate therapies for rhinovirus. Encouragingly, it is found that during rhinovirus-induced immunoreactions the levels of certain cytokines in patients' serum will alter. These cytokines may have pivotal pro-inflammatory or anti-inflammatory effects via their specific mechanisms. Thus far, studies have shown that inhibitions of cytokines such as IL-1, IL-4, IL-5, IL-6, IL-13, IL-18, IL-25, and IL-33 may attenuate rhinovirus-induced immunoreactions so that relieving rhinovirus infection. Furthermore, such therapeutics for rhinovirus infection can be applied to viruses of other species, with certain practicability.